2021
DOI: 10.1002/14651858.cd013495.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Approaches for discontinuation versus continuation of long-term antidepressant use for depressive and anxiety disorders in adults

Abstract: Approaches for discontinuation versus continuation of long-term antidepressant use for depressive and anxiety disorders in adults (Review)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
66
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(77 citation statements)
references
References 248 publications
0
66
0
1
Order By: Relevance
“…The risk of relapse during and after discontinuation is realistic but seems to be lower than estimated by our GPs. An important group of people on long-term antidepressants can stop the antidepressant [ 27 ]. There is also evidence that when supported by psychotherapy, 40–75% of people with recurrent depression are able to discontinue their antidepressants [ 28–30 ].…”
Section: Discussionmentioning
confidence: 99%
“…The risk of relapse during and after discontinuation is realistic but seems to be lower than estimated by our GPs. An important group of people on long-term antidepressants can stop the antidepressant [ 27 ]. There is also evidence that when supported by psychotherapy, 40–75% of people with recurrent depression are able to discontinue their antidepressants [ 28–30 ].…”
Section: Discussionmentioning
confidence: 99%
“…We must first acknowledge that there is a paucity of evidence to answer this question: in a recent Cochrane review only 33 randomised controlled trials examining antidepressant discontinuation were identified. 44 The majority of these were uninformative because they mostly stopped antidepressants abruptly or in less than 4 weeks, only one measured withdrawal symptoms, and most were at high risk of bias because detection of relapse was confounded by withdrawal symptoms. 44 There are observational trials that have found that tapering antidepressants over months and to doses much lower than those used in clinical practice generally have better outcomes than tapering over weeks to 25% or 50% of the dose of currently available tablet formulations.…”
Section: How To Discontinuementioning
confidence: 99%
“…44 The majority of these were uninformative because they mostly stopped antidepressants abruptly or in less than 4 weeks, only one measured withdrawal symptoms, and most were at high risk of bias because detection of relapse was confounded by withdrawal symptoms. 44 There are observational trials that have found that tapering antidepressants over months and to doses much lower than those used in clinical practice generally have better outcomes than tapering over weeks to 25% or 50% of the dose of currently available tablet formulations. 55 In particular, one observational study found that reducing doses over months down to as low as 0.5% of clinically used doses (eg, 0.1 mg of paroxetine and 1 mg of venlafaxine) allowed the majority (71%) of a group of patients to cease their antidepressant.…”
Section: How To Discontinuementioning
confidence: 99%
“…Several studies have been conducted to investigate interventions that support the discontinuation of psychotropic medication and identify effective interventions that minimise the risk of relapse and withdrawal symptoms [20][21][22] . In many cases, the existing evidence base is limited.…”
Section: Psychotropic Medications Have Various Adverse Effectsmentioning
confidence: 99%